PENERAPAN PENDEKATAN MULTIPLE INTELLIGENCES DALAM PEMBELAJARAN BERDIFERENSIASI UNTUK MENGOPTIMALKAN KECERDASAN LINGUISTIK DI KELAS V - Oktamia Suci, Lidya; Dwi Puspita, Ryan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abstract Learning in elementary schools tends to use a conventional approach, thus under-facilitating the diversity of student intelligence. This study aims to describe the application of the multiple intelligences approach in differentiated learning to optimize the linguistic intelligence of fifth-grade students. This study used a descriptive qualitative research method with 27 fifth-grade students as subjects. Data collection techniques included observation, questionnaires, and documentation. Data analysis techniques used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research findings indicate that the application of the multiple intelligences approach in differentiated learning is carried out in three main stages. The first stage is preparation, which includes initial observations, theoretical review, instrument development, identification of linguistic intelligences, and lesson design. The second stage is the implementation of learning over three meetings, which includes recognizing feelings, station rotation based on multiple intelligences, and presentation of work results and reflection. The third stage is post-implementation, which includes data processing and analysis, triangulation, and report preparation. The research results show that the application of the multiple intelligences approach in differentiated learning has provided a varied and responsive learning experience to the diversity and unique potential of each student and demonstrated positive student activity and responses. Overall, this approach is effective in optimizing the linguistic intelligence of fifth-grade students through the differentiation of content, process, and product using the station rotation model. Keywords: Differentiated Learning, Linguistic Intelligence, Multiple Intelligences